Effectiveness of Peer Coaching to Enhance Pre-Service Teachers' Self-Efficacy toward Science Instruction and Pedagogy Content Knowledge - Dudley, Kelli Provence (My University, 2018)
Peer coaching, specifically its role in influencing pedagogical content knowledge and self-efficacy of pre-service teachers (PSTs) regarding teaching science in early education is examined. First, this study proposes a theory to increase pre-service teachers' pedagogical content knowledge by merging the constructivist theory of cognitive development (Piaget, 1952; Vygotsky, 1978), with Bandura’s (1997) self-efficacy theory. Combining the two theories broadens the construct and enriches the preparation of pre-service teachers. Incorporating a peer coaching model as a tool to understand the importance of building the pre-service teachers’ science self-efficacy together with the construction of knowledge plays a critical role in developing the pedagogical content knowledge of pre-service teachers. Second, a mixed methods phenomenological study utilized observations, reflective journals, recorded post-conferences, class discussions, and a field notebook to gather qualitative data, and the Science Teaching Efficacy Belief Instrument-Pre-service (STEBI-B) was administered to gather quantitative data (Enochs & Riggs, 1990). Participants included 26 PSTs enrolled in a university primary science methods course and a 60-hour primary practicum in fall 2017. The fall 2016 course was completed by 19 PSTs that served as the comparison group for this research. This study found peer coaching to be an effective tool to increase PSTs’ self-efficacy and pedagogical content knowledge. Third, this dissertation provided practical strategies for implementing one model of peer coaching in teacher education methods courses.
Keywords: Science, peer coaching, pre-service teachers, early childhood